Probability mapping of petroleum occurrence with a multivariate-Bayesian approach for risk reduction in exploration, Nanpu Sag of Bohay Bay Basin, China - Suyun, Hu; Qiulin, Guo; Zhuoheng, Chen; Shiyun, Mi; Hongbin, Xie (Bogucki Wydawnictwo Naukowe, 2009)
A multivariate-Bayesian approach has been applied to the Nanpu Sag of the Bohai Bay Basin, eastern China, to evaluate probability of oil occurrence. The geological data from 343 exploratory wells and seismic interpretations that were available at the end of 2004 were used for the purpose. Seventeen wells were drilled after the evaluation in 2005, sixteen of which reached their target horizon. Eight of the nine wells drilled in areas with a predicted high probability of hydrocarbon occurrence (>50%) encountered commercial oil, indeed; post-drilling analysis indicated that seven of these eight wells yielded high flow rates from thick net pay, and that one of these wells yielded a low flow rate. Seven wells were drilled in areas with a predicted relatively low probability (<50%) of oil occurrence; three of them were dry and four recovered oil with relatively low flow rates. Comparison of the post-drilling results with the pre-drilling prediction suggests that the multivariate-Bayesian approach can help visualize geological risk, thus improving exploration success by optimizing the drilling strategy.
Keywords: Oil exploration; Risk visualization; Well planning; Nanpu Sag; Probability map